O Fenômeno da uberização das relações de trabalho: análise jurisprudencial da relação empregatícia de motoristas de uber nos processos trabalhistas do Tribunal Regional do Trabalho da Terceira Região - COSTA, Felipe Araujo (2022)
This work aims to analyze the laber activity of Uber drivers under the optics of uberization. The technologies avance in the contemporaneity produces disruptive faces in work relationships, suffering influences by the technologic development. The massification of communications and information technologies changes the work organization for the uberization phenomenon, with potencial of expansion to many human labor areas. From the perspective of labor law, the labor activity from uber drivers faces against obstacles for your caractherizacion like employment relation. To formulate jurispridential understanding about the theme, annalyse ninety nine national law suits and two international that aims to describe that labor activity as work relationship. Concludes through constatation of fragilization of work relationships contemporary in function of the jurispridential negative of recognition of work relationships.